Comparison of 7 surgical interventions for recurrent lumbar disc herniation: A network meta-analysis and systematic review - Hang Zhang; Junmao Gao; Qipeng Xie; Mingxin Zhang (PLoS ONE, 2025)
Study design Network meta-analysis of multiple treatment comparisons of recurrence lumbar disc herniation. Objective The purpose of comparing the differences between different surgical approaches for recurrent lumbar disc herniation (LDH). Methods The PubMed, Embase, MEDLINE, Cochrane Library, Web of Science, Google Scholar and China National Knowledge Infrastructure databases were searched for articles published before April 10th, 2024. The Markov chain Monte Carlo methods were used to perform a hierarchical Bayesian NMA in R version 4.3.3 using a random effects consistency model. The assessing outcomes were pain intensity, disability, complications and recurrence. Results 20 studies including 1556 patients and 7 different approaches (PELD, MED, MIS-TLIF, TLIF, Unilat -TLIF, PLIF and OD) were retrospectively retrieved. the efficacy of each approach was the same in relieving pain, OD was significantly better than PELD and MIS-TLIF in relieving dysfunction (SMD: 1.9[0.21,3.4] and 2.0[0.084,3.8], respectively), In addition, MIS-TLIF was significantly lower than PELD and MED in the complication rate (SMD: 0.37[0.14,0.84] and 0.15[0.034,0.68], respectively), TLIF was significantly Lower than MED in the complication rate (SMD:0.14 [0.027,0.70]), PELD was significantly higher than MIS-TLIF, TLIF and PLIF in the recurrence rate (SMD: 1.3e-17 [2.4e-44,0.00016],1.2e-12[2.1e-36,0.34] and 1.4e-12[6.2e-35,0.013], respectively), MED was significantly higher than MIS-TLIF and PLIF in the recurrence rate (SMD: 2.6e-17[5.6e-44,0.0037] and 3.1e-12[1.6e-34,0.022], respectively), OD was significantly higher than MIS-TLIF, TLIF and PLIF in the recurrence rate (SMD:4.6e+16[2.3e+02,3.0e+43], 4.3e+11[2.4,2.5e+35] and 4.1e+11[35,8.7e+33], respectively). Conclusions In the treatment of recurrent lumbar disc herniation, vertebral fusion surgery is superior to repeat discectomy. At the same time, MIS-TLIF may be a preferable surgical procedure in the treatment of recurrent lumbar disc herniation.